Experiencia colombiana en reparación de núcleos de transformadores de potencia (2015)
This article presents a case report about faults presented in power transformer cores and shows some technical and methodological experiences in partial and total repair to several units, carried out in Industrias Explorer Ingeniería S.A.S, a company dedicated to the maintenance and repair of power transformers. The methodology for the selection of foil type, court system, assemble, adjustment and pressing of the core are also presented, since these activities are crucial to get an equipment with fewer no-load losses, as well as lower levels of noise. The stages for the magnetic flux density calculation, test circuit for core saturation, considerations to thermographic inspection and no-load losses measurement, type foil selection and assembling technique employed are described. Some experiences are presented: partial core reposition, replacement core isolation of affected areas using Nomex fibers between sheets, total core replacement due to failure caused by poor cutting during manufacturing process, replacement of total core due to failure caused by double grounding that produced heating of it affecting the interlamination isolation between their sheets placing them in shortcut. In all cases there is a reduction on no-load losses. Finally the performance of power Transformers after been in service is presented and described.